MODEL PENGENDALIAN MUTU LAHAN KERING BERBASIS PEMBERDAYAAN MASYARAKAT DI KABUPATEN PONOROGO - Rimun Wibowo; Sjafri Mangkuprawira; Asep Saefuddin; Sumarjo Gatot Irianto (Graduate School Bogor Agricultural University (SPs IPB), 2012)
To control quality of rainfed areas as well as improvement of farmers’ welfare is efforts already has been done by local government (Ponogoro) however it’sstill not success yet because it used to partial approach. Therefore, it is very important to research and develop model how to control quality of rainfed based on community empowerment with integrated (system) approach.The location of research is in Ponorogo Districtwith 326 respondens, consist of 6experts, 20 linkage agencies staff and 300 farmers. Beside useAnalytical Hierarchy Process (AHP), Interpretative Structural Modelling (ISM), and System, this research also use univariat and bevariate analyze (Chi- Square and Structure Equation Model- SEM).Based on data and information that collected and analyzed, this research develop model that reflected the the real situation (fact), that can be simulated and validated. The model is established with system approach of population, local government services and ecology. The model validated by absolute mean error (AME) and absolute variation error (AVE) that reflected variance between actual and value from model less than 10%, it show the model is a valid.This mean model able to simulate any changing of rainfed areas quality control both in short or long term period.Other significant factors that related with rainfed areas quality control is farmers knowledge (p-value= 0,030) and farmers behavior (p-value=0,040).The empowerment of farmers indicated by food and nutrition security (γ = 1), settlement and sanitation security (γ = 0.23), healthy security (γ = 0.01)and education security (γ = 0.24). The empowerment of farmers influenced by coping strategy (β=0.41), that reflected by how farmer survive in production, consumption and marketing of agriculture with respective of γ is0.59, 0.27, 037 and 0.42. In line with these statistic analysis AHP, ISM results and validation model, this research formulated empowerment policy focus on life skill development through farmer group. In the beginning process of life skill development focus on soft skill and then hard skill later on up to achieve sustainable self help group in managing their rainfed areas.Keywords: rainfed, quality, control, empowerment, model, system, coping strategy